Force and power in rowing - Kleshnev, V. (Rowing Biomechanics Newsletter, 2014)
Coaches and rowers quite often mismatch the terms `force` and `power` and use `power curve` to mean `force curve`. Also, they say `power strokes` meaning a drill with maximal force application at low stroke rates, quite often with a water brake. In fact, the power in this drill is not very high because of low speed and stroke rate. The article trys to refresh the basics and promote correct usage of biomechanical terminology.